SURGICAL TREATMENT PRINCIPLES IN PERIAPICAL ENDODONTIC PATHOLOGY - Constantin Mihai; Cristian Constantin Budacu; Gabi Topor (Romanian Society of Oral Rehabilitation, 2019)
The fact that apical periodontitis is one of the most thorny problems of endodontic therapy, determine sus to consider it necessary to understand some aspects of diagnosis in order to achieve the procedures that have the greatest chances of maintaining the pulp and periapical affected teeth. Incorrectly treated pulp infections will cause complications in apical periodontium which is located below the tooth. The microbes present in the infected pulp can diffuse into surrounding tissues through the hole at the tip of the root (called apex) causing acute or chronic infections. Apical periodontitis are most often complications of the pulp gangrene, which is an important factor of infection, able to maintain remote illnesses (nephritis, myocarditis, endocarditis, rheumatic diseases). Material and method: The study carried out in order to achieve the proposed objectives included a total of 191 patients solved in the Oral and Maxillofacial Surgery Clinic (Ambulator), from the University Polyclinic of the Faculty of Dental Medicine in Iaşi, between 1.01.2014-01.12.2018. Results and discussions: Since the main cause of periapical inflammation is of an endodontic nature, surgical treatment can not be considered as the first choice because it does not debride the root canal, as it is the endodontic therapy. Periapical surgery should never be performed before conventional non-surgical canal treatment has been performed. Conclusions: The major indication of apical resection is found at the level of the frontal teeth group, especially the central incisors. These teeth, due to endodontic characteristics, are well suited to conservative endodontic treatment. The need for surgery is probably the result of a failure of conservative treatment, a technical mistake, or the convenience of a practitioner who prefers to resort to surgery before even tending conservative treatment.